Feathermeal/bloodmeal liquid suspensions for calves grazing winter wheat pasture - Kuhl, Gerry L.; LeValley, G.E. Jr.; McCormack, G.D.; Blasi, Dale A.; Drouillard, James S.; Newdigger, Glenn E., Jr. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A field study was conducted over 2 years at four different locations in south central Kansas to compare a feathermeal/bloodmeal (ESCAPE) liquid suspension to a molasses-based liquid supplement (ENERGY) and a dry mineral supplement (CONTROL) on the liveweight gain of 768 calves grazing wheat pasture. No significant differences occurred in supplement intake between ESCAPE and ENERGY across years (P=.88). Offering a liquid supplement containing either ES CAPE or ENERGY did not improve (P=.91) growth performance relative to CONTROL calves.
Keywords: Beef; Wheat pasture; Feathermeal; Liquid suspensions